2005
DOI: 10.3354/meps291081
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of sympatric seahorse species along a gradient of habitat complexity in a seagrass-dominated community

Abstract: We present estimates of local population abundance, distribution and habitat preference for 2 European seahorse species, Hippocampus guttulatus and H. hippocampus. We predicted that these sympatric species would partition their habitat into 2 broadly defined habitat types: complex vegetated habitats and sparsely vegetated sand flats. We sampled populations using underwater visual census techniques over landscape (100s to 1000s m) and microhabitat scales (<1 m). Over landscape scales, we estimated abundance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
209
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(232 citation statements)
references
References 51 publications
19
209
2
2
Order By: Relevance
“…Low numbers of juveniles were found for both Hippocampus bargibanti and H. denise, which is similar to findings for other seahorse species (Bell et al 2003, Curtis & Vincent 2005, Martin-Smith & Vincent 2005, Rosa et al 2007. The record of a recently settled juvenile male H. denise in the present study, at 13 mm SL, indicates that sexual maturity is attained soon after settlement.…”
Section: Discussionsupporting
confidence: 90%
“…Low numbers of juveniles were found for both Hippocampus bargibanti and H. denise, which is similar to findings for other seahorse species (Bell et al 2003, Curtis & Vincent 2005, Martin-Smith & Vincent 2005, Rosa et al 2007. The record of a recently settled juvenile male H. denise in the present study, at 13 mm SL, indicates that sexual maturity is attained soon after settlement.…”
Section: Discussionsupporting
confidence: 90%
“…This is probably due to the fact that the western part of the lagoon is in direct Uncommonly for this species, we found only 3 specimens of Hippocampus guttulatus on algal meadows. Other researchers (Foster and Vincent 2004, Curtis and Vincent 2005, 2006, Vincent et al 2011 reported that H. guttulatus inhabited seagrass-or algal beds. The presently reported study is also in partial disagreement with the recent work of Gristina et al (2014), who also studied the Mar Piccolo of Taranto.…”
Section: Discussionmentioning
confidence: 99%
“…While juveniles may have been missed due to a planktonic stage it is unclear as to why seahorses between 3-5 cm were not recorded. Other fisheries studies also show that intervening size classes between small juveniles and adults of several marine fish including two species of seahorses (H. guttulatus and H. hippocampus) are rarely seen in benthic surveys and plankton tows (Pérez-Ruzafa et al, 2004;Curtis & Vincent, 2005). While smaller seahorses may have been missed due to the sampling methodology they may be utilizing a different habitats has been observed in H. comes in the Philippines (Perante, 2002;Morgan & Vincent, 2007).…”
Section: Sizementioning
confidence: 99%